Consensus Statement on High-Intensity Focused Ultrasound for Functional Neurosurgery in Switzerland - Stieglitz, Lennart H.; Oertel, Markus F.; Accolla, Ettore A.; Bally, Julien; Bauer, Roland; Baumann, Christian R.; Benninger, David; Bohlhalter, Stephan; Büchele, Fabian; Hägele-Link, Stefan; Kägi, Georg; Krack, Paul; et al. (Frontiers in Neurology, 2021)
Background: Magnetic resonance-guided high-intensity focused ultrasound (MRgHiFUS) has evolved into a viable ablative treatment option for functional neurosurgery. However, it is not clear yet, how this new technology should be integrated into current and established clinical practice and a consensus should be found about recommended indications, stereotactic targets, patient selection, and outcome measurements. Objective: To sum up and unify current knowledge and clinical experience of Swiss neurological and neurosurgical communities regarding MRgHiFUS interventions for brain disorders to be published as a national consensus paper. Methods: Eighteen experienced neurosurgeons and neurologists practicing in Switzerland in the field of movement disorders and one health physicist representing 15 departments of 12 Swiss clinical centers and 5 medical societies participated in the workshop and contributed to the consensus paper. All experts have experience with current treatment modalities or with MRgHiFUS. They were invited to participate in two workshops and consensus meetings and one online meeting. As part of workshop preparations, a thorough literature review was undertaken and distributed among participants together with a list of relevant discussion topics. Special emphasis was put on current experience and practice, and areas of controversy regarding clinical application of MRgHiFUS for functional neurosurgery. Results: The recommendations addressed lesioning for treatment of brain disorders in general, and with respect to MRgHiFUS indications, stereotactic targets, treatment alternatives, patient selection and management, standardization of reporting and follow-up, and initialization of a national registry for interventional therapies of movement disorders. Good clinical evidence is presently only available for unilateral thalamic lesioning in treating essential tremor or tremor-dominant Parkinson's disease and, to a minor extent, for unilateral subthalamotomy for Parkinson's disease motor features. However, the workgroup unequivocally recommends further exploration and adaptation of MRgHiFUS-based functional lesioning interventions and confirms the need for outcome-based evaluation of these approaches based on a unified registry. MRgHiFUS and DBS should be evaluated by experts familiar with both methods, as they are mutually complementing therapy options to be appreciated for their distinct advantages and potential. Conclusion: This multidisciplinary consensus paper is a representative current recommendation for safe implementation and standardized practice of MRgHiFUS treatments for functional neurosurgery in Switzerland.